137k views
1 vote
Use the substitution method to solve
3x + 2y=12
y=2x -1​

User Arti
by
4.9k points

2 Answers

3 votes

Answer:

the solution is : (2 , 3)

Explanation:

hello : here is an solution

3x + 2y=12.....(*)

y=2x -1​.....(**)

put the value for y in (*) :

3x + 2(2x-1)=12

3x+4x-2 = 12

7x =14

so : x =2

but : y=2x -1

y =2(2)-1 = 3

the solution is : (2 , 3)

User Xappymah
by
5.1k points
4 votes

Answer:

1. y=2

2. y= - 2

Explanation:

Thats my answer hope it helps

User First Zero
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.